Essays on aviation, regional economic development, and migration - Kalandarova, Ulmaskhon, author; Pena, Anita Alves, advisor; Weiler, Stephan, advisor; Tavani, Daniele, committee member; Graff, Gregory, committee member (Colorado State University. Libraries, 2025)
Aviation is an important factor of promoting regional development. Its impact to the economy could be analyzed from various angles, including through the effect of airports to local and regional economies, and through the effects of novel aviation fuels to the local economies and sustainability, in general. The first two essays in this dissertation examine the effect of aviation from those above-mentioned angles to local economies in Colorado and California. The third essay focuses on the phenomenon of migration and remittances during the post-Soviet era in Tajikistan, a country in Central Asia. Motivated by reverse causality issue between airport development and regional economic growth, in Chapter 1, titled as "Air Transportation and Regional Economic Development in Colorado", we examine the dynamic causal relationship between air transportation at Denver International Airport (DIA) and regional economic development for the Denver MSA and the overall state of Colorado using time series methods for the period from 2000 to 2019. The results reveal overall positive effects of air transportation on local regional development in the Denver MSA with muted effects for the state of Colorado as a whole, consistent with impacts fading for more remote areas. Estimation of VECM models and Impulse Response Function reveals bi-directional, positive, significant long-run causality between Total Domestic Flight Passengers and Total Business Entities in Denver: a 1% change in Total Domestic Flights Passengers leads to a 3% increase in Total Registered Businesses and this magnitude is higher than in the vice-versa case. Total Domestic Flight Passengers are also positively associated with local employment in Denver, in contrast to a negative effect for the larger Colorado region in the short-run. A 1% change in Total Domestic Flights Passengers leads to a 0.006% increase in Total Non-Farm Employment in Denver and about a 0.004% decrease in Colorado broadly. Total Cargo affects employment positively both in Denver and beyond, estimated by both VAR model and Impulse Response Functions. The same 1% change in Total Cargo is associated with about a 0.007% increase in Total Non-Farm Employment in Denver and about a 0.005% increase in Colorado. The paper confirms traditional claims that airport services play an important role in local and regional development measured via both traditional employment and non-traditional business variables. Furthermore, comparison of the Denver MSA to the wider state illustrates differences associated to the distance to the hub city. Chapter 2, titled as "Inter-fuel Substitution in the Aviation Sector and Sustainable Aviation Fuel: Case study of California", explores the dynamics of inter-fuel substitution, focusing on the impact of biofuels in the aviation sector and their potential in decarbonizing aviation in California. Specifically, the research investigates two key objectives: (1) understanding the historical interplay of substitution or complementary relationships among general transportation fuels after the mid-2010's introduction of biofuels, and (2) evaluating the extent to which biofuel adoption drives inter-fuel substitution in particularly aviation sector. Ordinary Least Squares (OLS) and Seemingly Unrelated Regression (SUR) methods are used to analyze the data from U.S. Energy Information Administration (EIA) and U.S. Environmental Protection Agency (EPA) for 1980-2022 to provide a comprehensive view of biofuel integration. Results reveal that while biofuels have not significantly changed traditional substitution and complementarity relationships in the general transportation sector, they serve as a viable alternative to kerosene-based jet fuel in aviation. A 1% increase in jet fuel price leads to 1.043% increase of SAF volumes consumed, demonstrating that SAF has become a valid substitute for a traditional kerosine-based jet fuel. The effect of price changes of SAF on jet fuel volumes still remains limited because of small shares of biofuels in aviation. The paper demonstrates biofuels' growing potential to reduce dependency on fossil fuels and their important contribution to achieving long-term sustainability in aviation. Finally, in Chapter 3, titled as "Motives of Migration and Remittances in Tajikistan", we focus on migration phenomena in Tajikistan, analyzing what factors drive people to migrate from Tajikistan and to remit back to Tajikistan. Probit and Heckman sample selection correction methods are used to analyze migrant and household characteristics data from the World Bank's "Jobs, Skills, and Migration Survey in Tajikistan, 2013." Results reveal that migration cost variables like having networks and family arrangement of costs related to migration have a highest strong positive association with the probability of having migrants in the households, empirically reinforcing the evidence of how important migration networks and family arranged costs of migration are in shaping the migrations flows from Tajikistan to Russia, making diasporas important "non-formal" institutions between two countries. The college education and language skills variables reveal a negative association with the probability of having migrants in the households, complying with a Negative Selection migration process predicted by Roy's model (1951). Language skills demonstrate a positive association with the amount of remittances, since it makes easier to find a higher-paid job knowing the destination language, and so more remittances could be sent to Tajikistan. Also, family size and family income show a positive association with remittances transferred to households. Additionally, the results reveal that there is a significant selection bias (errors from two equations are correlated, lambda is negative and significant) and therefore Heckman estimation method usage is justified to correct for the self-selection bias.